Fabrication and characterisation of polyethersulfone/chitosan/non-ionic nanofiltration membrane for dyes removal - Johary F.; Zaimin F.F.M.; Rohani R.; Hassan A.R.; Sharifuddin S.S.; Mohd Hafez Mohd Isa (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS